The Effect of Inquiry Training Instructional Models Using Phet Media and Motivation toward Students Science Process Skill Junior High School Labuhan Deli Satu Atap Academic in 2022/2023 - Surya Darma; Indri Sari Nasution; Hasfan Fadli; Pesta Natalia (Universitas Muhammadiyah Enrekang, 2022)
This research aims : (1) to determine differences in students' science process skills who applied inquiry training instructional models using PhET media better than conventional models, (2) to determine differences between students science process skills who have high motivation better than students who have low motivation, (3) to determine the interaction between inquiry training instructional models using PhET media and conventional instructional models with a level of motivation in influencing students science process skill. The sample was taken using a cluster random class in which each class has an equal opportunity to be a sample. The first class applied inquiry training instructional models and the second class as a class of control applied conventional instructional models. The variables in this study are: (1) The independent variable is the inquiry training instructional models, (2) a moderator variable is the motivation of students, and (3) The dependent variable is the students' science process skills. The instrument used in this study is an instrument to know the motivation of students consisting of 25 questions and an instrument science process skills that consists of 10 questions that are declared valid and reliable. Results of the research showed that: (1) The students' science process skills who gave inquiry training instructional model is better than the conventional instructional model; (2) the science process skills of students who have high motivation were better than students who have low motivation; (3) there is the interaction between the learning model inquiry training and motivation toward science process skills of students.